Pengaruh Verifikasi Data Nasabah Kredit UMKM dan Nilai yang Diberikan untuk Menghindari Kredit Bermasalah - W, Christophorus Angga; Roestiono, Harry (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Variable used for this study consists of two variables independent that is Data Verification Influence of Micro, Small, and Medium Business Credit and Value Of Guarantees Provided with one variable dependent that is Avoid Problem Loans. Period of research conducted on quarterly financial statements from 2016-2017. Method used in this research is descriptive method. This study intend to find out the effect of verifying the exact data and value of guarantee provided by the debtor capable to avoid problem loans in the future. The study results showed that consumers verification data and the type of guarantee able to make debtor avoid problem loans, it proven from decreased number of total problem loans during 2016 – 2017, although total credit still increase significant.